Real estate investment decisions in COVID-19 crisis : the effect of perception and behavioral biases - Muhammad, Ali; Leong, Choi Meng; Eugene Aw, Cheng Xi; Puah, Chin Hong; Abdulkadir, Barut (Emerald Publishing Limited, 2023)
Purpose – This study aims to examine the interconnectedness between investors’ perceptions of assets and their behavioral factors with investment decisions during the COVID-19 pandemic in the real estate business in Pakistan. In this regard, this study predicted investment decisions using individuals’ perceptions of the asset (perceived asset quality, perceived asset price and perceived asset value [PAV]),and behavioral biases (overconfidence [OC], herding [HD], disposition effect [DE] and risk aversion [RA]). Design/methodology/approach – This study used a survey-based instrument to gather a total of 189 usable samples. The sample data were analyzed using partial least square structural equation modeling. Findings – The findings of this study indicated that PAV, OC and HD significantly predicted the investment decision, whereas DE and RA had an insignificant impact on investment decisions in the real estate business. In addition, this study found that PAV is the most important factor to predict investment decisions in real estate during the COVID-19 crisis. Originality/value – The authors are certain that the study findings reinforce policy implications for regulators, policymakers and financial institutions. The study findings are also useful and relevant if the real estate sector experiences a crisis in the future.